1989
DOI: 10.1104/pp.91.2.679
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Phosphate Concentration Is Low during Feedback Limited Photosynthesis

Abstract: It has been hypothesized that photosynthesis can be feedback limited when the phosphate concentration cannot be both low enough to allow starch and sucrose synthesis at the required rate and high enough for ATP synthesis at the required rate. We have measured the concentration of phosphate in the stroma and cytosol of leaves held under feedback conditions. We used nonaqueous fractionation techniques with freeze-clamped leaves of Phaseolus vulgaris plants grown on reduced phosphate nutrition.Feedback was induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 25 publications
5
125
0
1
Order By: Relevance
“…Chl, the chloroplast marker, occurred in the upper, lightest, fractions; the greatest percentage of vacuolar marker (␣-mannosidase) occurred in the lower, heaviest, fractions; and the cytosolic marker (phosphoenolpyruvate carboxylase) generally partitioned toward the middle of the gradient. This relative distribution of compartment markers is typical for plant leaves after centrifugation in nonaqueous gradients (Gerhardt and Heldt, 1984;Sharkey and Vanderveer, 1989;Stitt et al, 1989;Moore et al, 1995). In comparison with the distribution of markers, DMAPP was predominately associated with Chl.…”
Section: Cellular Localization Of Dmappmentioning
confidence: 66%
See 2 more Smart Citations
“…Chl, the chloroplast marker, occurred in the upper, lightest, fractions; the greatest percentage of vacuolar marker (␣-mannosidase) occurred in the lower, heaviest, fractions; and the cytosolic marker (phosphoenolpyruvate carboxylase) generally partitioned toward the middle of the gradient. This relative distribution of compartment markers is typical for plant leaves after centrifugation in nonaqueous gradients (Gerhardt and Heldt, 1984;Sharkey and Vanderveer, 1989;Stitt et al, 1989;Moore et al, 1995). In comparison with the distribution of markers, DMAPP was predominately associated with Chl.…”
Section: Cellular Localization Of Dmappmentioning
confidence: 66%
“…The nonaqueous fractionation procedures were similar to those reported elsewhere (Gerhardt and Heldt, 1984;Sharkey and Vanderveer, 1989). Sunexposed cottonwood (Populus deltoides) leaves were collected directly into liquid N 2 at midday.…”
Section: Nonaqueous Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of phosphorylated intermediates following the increase in CO 2 fixation will lower the levels of free Pi in both the cytosol and the chloroplasts. Low stromal levels of Pi lead to an inhibition of photosynthesis (Sharkey & Vanderveer 1989; Rao & Terry 1995). Export of G6P would supplement TP export, increasing cytosolic substrates for sucrose synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study indicated that excessive NSC accumulation in leaves could cause a feedback inhibition of photosynthetic abilities on account of both decreasing sucrose synthesis and orthophosphate depletion in the cytosol (Araya et al, 2006). The orthophosphate depletion could suppress adenosine triphosphate synthesis and the reduction of phosphoglyceric acid to triose phosphate, and thereby suppress the photosynthesis rate (Sharkey and Vanderveer, 1989). Therefore, an excessive accumulation of starch, fructose and NSC in L. kaempferi leaves under P fertilization probably had a feedback inhibition effect on its photosynthesis rate .…”
Section: Non-structural Carbohydrates Of the Two Species Under N And mentioning
confidence: 99%